0481 Higher Risk Of OSA Is Associated With Poorer Affect Regulation Among The Severely Mentally Ill With A History Of Aggression: Evidence From A Forensic Setting. (12th April 2019) - Gosselin, Anik; Geck, Celia; Lee, Elliott; Robillard, Rebecca; Douglass, Alan; Smith, Angela; Koninck, Joseph De
Abstract: Introduction: Obstructive sleep apnea (OSA) is a sleep-related breathing disorder with negative consequences on daytime functioning, including fatigue, irritability, and poorer memory. OSA is highly prevalent among individuals diagnosed with severe mental illnesses (SMI), likely due to an accumulation of risk factors (e.g., antipsychotics, obesity, smoking). Psychiatric patients in forensic settings display greater impulsivity and emotional dysregulation compared to non-forensic psychiatric patients. We hypothesized that forensic patients at higher risk of OSA will display greater impulsivity, aggression and emotional dysregulation than forensic patients at low risk of OSA. Methods: Study participants were male (n=55) and female (n=10) forensic patients (mean age = 38.5 ±11.5). All were diagnosed with at least one SMI (e.g., schizophrenia, bipolar disorder). Participants completed the Sleep Disorders Questionnaire 2 - Sleep Apnea subscale (SDQ-2-SA) to estimate risk of OSA, followed by other self-report surveys, including: Pittsburgh Sleep Quality Inventory (PSQI), Epworth Sleepiness Scale (ESS), Buss-Perry Aggression Questionnaire (BPAQ), Barratt Impulsiveness Scale (BIS), Depression Anxiety and Stress Scale (DASS), Difficulties in Emotion Regulation Scale (DERS). Correlation analyses were run to examine the relationship between SDQ-2-SA scores and the scores from the surveys measuring different aspects of affect as well as sleep quality and sleepiness. Results: Higher risk of OSA (as per the SDQ-2-SA) was positively correlated with poorer sleep (PSQI; r=0.34, p <.01); higher aggression (BPAQ, r=0.25, p <.01), higher impulsivity (BIS, r=0.35, p <.01), higher depression and anxiety (DASS, r=0.42, p <.001), and greater emotion dysregulation (DERS, r=0.36, p <.01). Higher risk of OSA was not correlated with sleepiness. Conclusion: While this remains to be replicated with objective PSG data, the present findings highlight that emotional dysregulation, impulsivity and aggression in forensic patients with various SMI may be worsened by OSA, a condition often undiagnosed and untreated among forensic patients. Future studies should investigate whether appropriate treatment in forensic patients with OSA may help improve emotional regulation, impulsivity and aggression, common features in many psychiatric disorders. Support (If Any): UMRF